The association between social media use and body dysmorphic symptoms in young people - Gupta, Monica; Jassi, Amita; Krebs, Georgina (Frontiers in Psychology, 2023)
Introduction: Social media use (SMU) is highly prevalent amongst young people and previous research suggests an association with mental health problems, including poor body image. However, the potential relationship between SMU and body dysmorphic disorder (BDD) has received little attention. Furthermore, little is known about the factors that moderate the potential association between SMU and body dysmorphic symptoms. The current study tested the associations between three facets of SMU and body dysmorphic symptoms and explored perfectionism as a moderator in a non-clinical sample. Method: Two-hundred and nine 16-18year-olds (mean age = 16.5 years, 37% male) recruited from schools in London completed an online survey measuring aspects of SMU, including: frequency of image-and text-based SMU; motivations for SMU (appearance, popularity, connection or values and interests); and active and passive SMU. Participants additionally completed validated measures of body dysmorphic symptoms, perfectionism, and anxiety/depressive symptoms. Linear regression models tested the association of body dysmorphic symptoms with different facets of SMU, with and without adjustment for age, sex and anxiety/depressive symptoms. Results: Frequency of use of imagebased, but not text-based, platforms was significantly and positively associated with body dysmorphic symptoms, and this association remained significant in the adjusted models.Appearance-based motivation for SMU was the only motivator uniquely associated with body dysmorphic symptoms across the unadjusted and adjusted models. Passive, not active, SMU was associated with body dysmorphic symptoms in unadjusted models, but this association became non-significant in the adjusted models. Self-oriented perfectionism moderated the association between frequency of image-based SMU and body dysmorphic symptoms. Discussion: Imagebased SMU, and appearance-based motivations for SMU, are positively associated with body dysmorphic symptoms. Self-oriented perfectionism may amplify the relationship between SMU and body dysmorphic symptoms. Our findings highlight the importance of a nuanced approach to examining SMU, and the need for further research to determine whether specific facets of SMU contribute to the development and/or maintenance of body dysmorphic symptoms.